Genealogical study using mitochondrial DNA - Lora, Anak Johi (Universiti Malaysia Sarawak (UNIMAS), 2011)
This study examines the inheritance of maternal mitochondria DNA of a selected family. The sequence analysis was done by analyzing the mitochondrial D-loop region which are the hypervariable region I (HVR I), hypervariable region II (HVR II) and hypervariable region III (HVRIII). A total of 54 buccal cell samples collected from 54 individuals of the selected family. Phylogenetic analysis was done using bootstrap test of Neighbor- Joining (NJ) and pairwise distance was to determine the genetic distance among the family members. The result of the phylogenetic analysis indicated that HVR I was the most hypervariable region compared to HVR II and HVR III. However, the combinations of the entire three HVR regions produce the best results regarding the genealogical relationship among individual members of the family